Genetic characterization of the metK locus in Escherichia coli K-12. - Hunter, J S (1975)
Three independently isolated metK mutants have been shown to have leisions lying between speB and glc near 57 min on the Escherichia coli chromosome. Two deletions result in a lack of the metC gene product but neither extends into the metK glc region. The three metK mutations are recessive to the wild-type allele carried on the KLF16 episome.